Nuclear accidents and policy: Notes on public perception - Felix Richter; Malte Steenbeck; Markus Wilhelm (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Major nuclear accidents as recently in Fukushima set nuclear power plant security at the top of the public agenda. Using data of the German Socio-Economic Panel we analyze the effects of the Fukushima accident and a subsequent government decision on nuclear power phase-out on several measures of subjective perception in Germany. In the light of current political debates about the strategic orientation of this energy turnaround, such an analysis is of particular interest since non-pecuniary gains in measures of subjective perception might provide further aspects to be taken into consideration when evaluating the economic costs of the policy. We find that the Fukushima accident increases the probability to report greater worries about the environment. Furthermore, we find evidence for a decrease in the probability to be very worried about the security of nuclear power plants as well as for an increase in reported levels of subjective well-being following the government's resolution on nuclear phase-out. Finally we find that the probabilities of reporting very high concerns are related to the distance between the respondents' place of residence and the nearest nuclear power station.
Keywords: I3; N7; Q4; R1; 330; Fukushima; nuclear accident; nuclear energy; nuclear phase-out; environment; subjective perception